The stock market’s reaction to the mandatory disclosure of ESG information - Col Lopes, Mateus Del; Jucá, Michele Nascimento (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: Analyze the impact of mandatory disclosure of ESG information in Brazil on the price of shares in the local market. Methodology: This analysis is carried out through an event study, which refers to the publication of the Reference Form (FRE) of companies in the metal and mining sector - that are environmentally sensitive. The date of the event is the date of disclosure of each company's FRE, for the fiscal year ending on December 31, 2022. Results: The results confirm the main hypothesis of this study: The mandatory disclosure of sustainability practices by Brazilian companies impacts the return on their shares. It is possible that the market understands that the short-term costs - related to the implementation of sustainability practices - still exceed the benefits that will lead to the appreciation of companies in the long term. However, the progressive integration of global markets foresees an alignment of sustainable practices that should reach the Brazilian market in the medium term. Contributions of the Study: This research differs from others by finding that the mandatory disclosure of sustainability practices - by Brazilian companies - negatively impacts the return on their shares, after the implementation of Resolution no. 59/2021. It contributes to academia with the empirical analysis of the market efficiency hypothesis. Furthermore, its results can help companies, investors and the capital market to better understand the initial effects of mandatory publication of sustainable practices. Finally, this study also contributes to the stimulation or adaptation of policies defined by regulatory bodies on sustainability issues.